2019
DOI: 10.3390/nano9101374
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Assessment of ITER-Like Tungsten Nanoparticles Using an In Vitro 3D Human Airway Epithelium Model

Abstract: The International Thermonuclear Experimental Reactor (ITER) is an international project aimed at the production of carbon-free energy through the use of thermonuclear fusion. During ITER operation, in case of a loss-of-vacuum-accident, tungsten nanoparticles (W-NPs) could potentially be released into the environment and induce occupational exposure via inhalation. W-NPs toxicity was evaluated on MucilAir™, a 3D in vitro cell model of the human airway epithelium. MucilAir™ was exposed for 24 h to metallic ITER-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 33 publications
(48 reference statements)
2
33
0
Order By: Relevance
“…A pro-inflammatory response is observed at day 1 and day 7 after exposure to the highest activity level, as indicated by the increase of IL-8 secretion. It is important to note that IL-8, though certainly not exhaustive of the inflammatory response pathway, was chosen as one of the most abundant pro-inflammatory mediators released by airway epithelial cells, shown to be upregulated by, e.g., nanoparticles of different kinds (19) including tungsten (8). This also makes it an ideal candidate for future adoption of this model for tritiated particles, as discussed later.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pro-inflammatory response is observed at day 1 and day 7 after exposure to the highest activity level, as indicated by the increase of IL-8 secretion. It is important to note that IL-8, though certainly not exhaustive of the inflammatory response pathway, was chosen as one of the most abundant pro-inflammatory mediators released by airway epithelial cells, shown to be upregulated by, e.g., nanoparticles of different kinds (19) including tungsten (8). This also makes it an ideal candidate for future adoption of this model for tritiated particles, as discussed later.…”
Section: Discussionmentioning
confidence: 99%
“…The MucilAir model mimics the upper respiratory tract structure of the human lung, including basal, goblet and ciliated cells. Representative TEM pictures of the tissue have been provided elsewhere, in our previously published work (8).…”
Section: Cell Culture and Cellular Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is noticeable that no NIR-irradiation did not trigger photocatalytic reactions and consequently did not cause toxicity to normal organs, and there was no toxic side effects of drug because no drug was used, reflecting the incomparable advantages of drug-free therapy in biosafety. Additionally, the toxicity of tungsten as a heavy metal is mainly demonstrated by soluble tungstates rather than by relatively more stable tungsten oxide and metal tungsten [40][41][42][43][44][45][46][47][48] , and therefore the development of tungsten oxide for biomedical applications is broadly being studies [42][43][44][45][46][47][48] where high biocompatibility with lowest toxic dose of 1000 mg/kg for oral administration was demonstrated. In this work, we also found that neither WO 3 nor SnS 1.68 -WO 2.41 exhibited obvious cytotoxicity (600 μg/mL, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have demonstrated an increase in inflammation and oxidative stress processes as well as histological impairments in rodent lungs after exposure of upper airways to tungsten (Roedel et al, 2012;Prajapati et al, 2017). Very recently, using two in vitro models, BEAS-2B cells and 3D human airway epithelium model, differential responses to tungsten were documented: epigenotoxic alterations and transient inflammatory response (George et al, 2019;Uboldi et al, 2019).…”
Section: Accepted Manuscriptmentioning
confidence: 99%